Kinetics of tau aggregation reveals patient-specific tau characteristics among Alzheimer's cases. Issue 2 (4th May 2021) - Kamath, Tarun V; Klickstein, Naomi; Commins, Caitlin; Fernandes, Analiese R; Oakley, Derek H; Frosch, Matthew P; Hyman, Bradley T; Dujardin, Simon
Abstract: The accumulation of tau aggregates throughout the human brain is the hallmark of a number of neurodegenerative conditions classified as tauopathies. Increasing evidence shows that tau aggregation occurs in a 'prion-like' manner, in which a small amount of misfolded tau protein can induce other, naïve tau proteins to aggregate. Tau aggregates have been found to differ structurally among different tauopathies. Recently, however, we have suggested that tau oligomeric species may differ biochemically among individual patients with sporadic Alzheimer disease, and have also showed that the bioactivity of the tau species, measured using a cell-based bioassay, also varied among individuals. Here, we adopted a live-cell imaging approach to the standard cell-based bioassay to explore further whether the kinetics of aggregation also differentiated these patients. We found that aggregation can be observed to follow a consistent pattern in all cases, with a lag phase, a growth phase and a plateau phase, which each provide quantitative parameters by which we characterize the aggregation kinetics. The length of the lag phase and magnitude of the plateau phase are both dependent upon the concentration of seeding-competent tau, the relative enrichment of which differs among patients. The slope of the growth phase correlates with morphological differences in the tau aggregates, which may be reflective of underlying structural differences. This kinetic assay confirms and refines the concept of heterogeneity in the characteristics of tau proteopathic seeds among individuals with Alzheimer's disease and is a method by which future studies may characterize longitudinal changes in tau aggregation and the cellular processes which may influence these changes. Abstract : In a reporter assay, Kamath et al. report differences in the kinetics of tau aggregation accross individuals in brain samples from sporadic Alzheimer patients reflecting the properties of the initial seeds and suggesting person-specific differences in tau pathobiology even among individuals with sporadic Alzheimer disease. Graphical Abstract: